Endothelial-Dependent and Independent Vascular Relaxation Effect of Tetrahydropalmatine on Rat Aorta - Zhou, Zhong-Yan; Zhao, Wai-Rong; Shi, Wen-Ting; Xiao, Ying; Ma, Zi-Lin; Xue, Jin-Gui; Zhang, Lun-Qing; Ye, Qing; Chen, Xin-Lin; Tang, Jing-Yi (Frontiers in Pharmacology, 2019)
Tetrahydropalmatine (THP) is an active natural alkaloid isolated from Corydalis yanhusuo W.T. Wang which has been widely used for treating pain and cardiovascular disease in traditional Chinese medicine. Previous studies suggested THP exist various pharmacological effects in neural and cardio tissue while the vascular reactivity of THP was not fully established. The present study found that THP concentration-dependently relaxed rat aorta which contracted by phenylephrine (Phe), KCl and U46619. The vascular relaxation effect of THP was partially attenuated by PI3K inhibitor wortmanin, Akt inhibitor IV, endothelial nitric oxide synthetase (eNOS) inhibitor L-NAME, guanylate cyclase inhibitors and the mechanical removal of endothelium. And the eNOS substrate L-argine reversed the inhibition effect of L-NAME on THP-induced vascular relaxation. THP also induced intracellular NO production in human umbilical vein endothelial cells. However, Pre-incubation with β-adrenergic receptor blocker propranolol, angiotensin II receptor 1 (AT1) inhibitor losartan, angiotensin II receptor 2 (AT1) inhibitor PD123319 or angiotensin converting enzyme inhibitor enalapril enhanced the vascular relaxation effect of THP. THP not affected the angiotensin II induced vascular contraction. Cyclooxygenase-2 (COX2) inhibitor indomethacin did not affect the vascular relaxation effect of THP. Furthermore, pre-treatment THP attenuated KCl and Phe induced rat aorta contraction in standard Krebs solution. In Ca2+ free Krebs solution, THP inhibited the Ca2+ induced vascular contraction under KCl or Phe stress and reduced KCl stressed Ca2+ influx in rat vascular smooth muscle cells. THP also inhibited intracellular Ca2+ release induced vascular contraction by blocking Ryr or IP3 receptors. In addition, the voltage-dependent K+ channel (Kv) blocker 4-aminopyridine, ATP-sensitive K+ channel (KATP) blocker glibenclamide and Inward rectifying K+ channel blocker BaCl2 attenuated THP induced vascular relaxation regardless of Ca2+-activated K+ channel (KCa) blocker tetraethylammonium. Thus, we could conclude that THP relaxed rat aorta in an endothelium-dependent and independent manner. The underlying mechanism of THP relaxing rat aorta involved in PI3K/Akt/eNOS/NO/cGMP signaling pathway, Ca2+ channels and K+ channels rather than COX2, β-adrenergic receptor and renin-angiotensin system (RAS). These findings indicated that THP might be potent treatment of disease with vascular dysfunction like hypertension.